1991
DOI: 10.1007/bf01887296
|View full text |Cite
|
Sign up to set email alerts
|

Peutz-Jeghers syndrome: CT and US demonstration of small bowel polyps

Abstract: A family affected with Peutz-Jeghers syndrome is reported with an emphasis on radiological findings. A patient showed extensive pigmentation around the lips, buccal mucosa, and nose. Another showed prolonged transient intussusception of a jejunal loop on barium meal examination, and massive rectal bleeding. In this patient, small bowel polyps could also be seen on ultrasonography (US) and computed tomography (CT). On CT several polyps, up to 3 cm in size, were detected along with a "carpeting" pattern of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 1 publication
0
5
0
3
Order By: Relevance
“…His past history revealed a diagnosis of slight anemia and hypoproteinemia probably associated with PJS, and an endoscopic examination that disclosed benign colonic polyps 6 years prior to the intussusceptions, but a diagnosis of PJS had not been made until he reached 41 years of age. At our hospital, the symptoms of intestinal obstructions led us to take plain X-rays of the abdomen, which revealed the obstructed small intestine, and a further examination by CT with contrast showed dilated loops of the small intestine and multiple concentric ring signs 8,9 with enhanced polypoid lesions. Those signs could also be demonstrated by ultrasonography of the abdomen as typical target signs.…”
Section: Discussionmentioning
confidence: 98%
“…His past history revealed a diagnosis of slight anemia and hypoproteinemia probably associated with PJS, and an endoscopic examination that disclosed benign colonic polyps 6 years prior to the intussusceptions, but a diagnosis of PJS had not been made until he reached 41 years of age. At our hospital, the symptoms of intestinal obstructions led us to take plain X-rays of the abdomen, which revealed the obstructed small intestine, and a further examination by CT with contrast showed dilated loops of the small intestine and multiple concentric ring signs 8,9 with enhanced polypoid lesions. Those signs could also be demonstrated by ultrasonography of the abdomen as typical target signs.…”
Section: Discussionmentioning
confidence: 98%
“…Clinical features in conjunction with radiologic findings and histologic specimens allow for a correct diagnosis to be made. Although the polyps are often detected with barium studies, they can also be identified with US or CT (11). Some authors have suggested using US or magnetic resonance (MR) imaging for follow-up imaging to reduce the lifetime radiation burden, with the caveat that small polyps less than 1.5 cm in diameter could be missed and clustered polyps could be misinterpreted as a larger mass lesion (12).…”
Section: Discussionmentioning
confidence: 99%
“…Early detection is especially important because PJS is a strongly predisposing condition for intussusception; in the worst cases, PJS patients run the risk of having to undergo repeated bowel resections. Direct visualization of polyps by US in PJS patients has been reported only once [3], and US and color Doppler findings of intussusception due to polyps in PJS have not been reported. In typical cases, the diagnosis of intussusception can be made by US or CT alone [5,6].…”
Section: Abdominal Imagingmentioning
confidence: 97%
“…In the literature, very little has been written about the US findings of PJS [3]. The color Doppler findings are also discussed.…”
mentioning
confidence: 96%